Equilibrium study for mercury removal using sub-bituminous coal and its application on ex-gold mining soil contaminated with mercury - Maulana, Amsar; Harianti, Mimien; Prasetyo , Teguh Budi; Herviyanti, Herviyanti (Brawijaya University, 2024)
Optimizing the potential utilization of low-rank coal, such as sub-bituminous coal (SC), can improve and maintain soil quality and productivity through amelioration technology. This potential is especially in controlling heavy metals such as Hg. This study aimed to examine the geochemistry of SC and the adsorption mechanism of Hg with SC through an adsorption isotherm model approach developed for experimental equilibrium. The geochemical of SC has an atomic composition of C (43.60%), O (40.64%), N (11.96%), Si (1.57%), Al (1.06%), Ca (0.92%), Mg (0.14%) and K (0.11%) and oxide composition dominated by SiO2 (57.07%), as well as O-H and N-H functional groups, C-H C-H, C=C-H, C=O, and C=C-H and minerals (quartz, magnetite, mica and muscovite). Characteristics of SC have a proximate composition (16.99% moisture, 97.81% volatile matter, 69.63% ash, and 28.19% fixed carbon) and chemical properties of pH, EC, CEC, OC, and total N (5.23, 1.38 dS m-1, 35.33 cmol(+) kg-1, 9.81% C, and 0.16% N). The adsorption capacity and coefficient of Hg2+ by SC were 304.32 mg g-1 and 78.67 L kg-1 at pH 1.26 and Hg2+ concentration 100 mg L-1 with a removal efficiency of 76.08%. Hg2+ adsorption isotherms occurred in Langmuir (RL = 0.97 and R² = 1)>Freundlich (1/n = 1.05 and R² = 0.9999) models. The application of 40 t SC ha-1 on ex-gold mining soil contaminated with Hg significantly decreased the total Hg in the soil by 2.50 mg kg-1 and a removal efficiency of 36.37% with increased pH H2O (0.35), OC (0.041% C), and CEC 2.14 cmol(+) kg-1, compared to control.